2007
DOI: 10.1021/ja0685295
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spin State Exchange Spectroscopy Reveals Equilibrium of Two Distinct Conformations of Leucine Zipper GCN4 in Solution

Abstract: The resonance assignment, secondary structure, and dynamic properties of a stable noncoiled coil conformation of the dimerization domain from yeast transcription activation factor GCN4 (Leu zipper; LZGCN4) are presented. Introduced in this paper, a new line of fully optimized spin state exchange experiments, XYEX-TROSY, applied to 1HN, 15N and 1Halpha,13Calpha moieties, established that in broad range of pH and buffer conditions the classical LZGCN4 coiled coil dimer is in a dynamic equilibrium with another di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 68 publications
2
37
0
Order By: Relevance
“…8,9 To elucidate which of the two conformations is responsible for the RNase activity, we sampled LZ-GCN4 RNA interactions under conditions where both dimeric and monomeric conformations are comparably populated (15 lM LZ-GCN4, pH 4.0). In the acidic environment, the presence of two distinct sets of resonances establishes that the dimeric and monomeric conformations are in the slow conformational exchange on the NMR chemical shift timescale (Supporting Information Fig.…”
Section: Catalytic Conformation Of Lz-gcn4mentioning
confidence: 99%
See 3 more Smart Citations
“…8,9 To elucidate which of the two conformations is responsible for the RNase activity, we sampled LZ-GCN4 RNA interactions under conditions where both dimeric and monomeric conformations are comparably populated (15 lM LZ-GCN4, pH 4.0). In the acidic environment, the presence of two distinct sets of resonances establishes that the dimeric and monomeric conformations are in the slow conformational exchange on the NMR chemical shift timescale (Supporting Information Fig.…”
Section: Catalytic Conformation Of Lz-gcn4mentioning
confidence: 99%
“…Our first aim was to elucidate which of the two LZ conformations (coiled coil dimer or partially structured monomer) 8 are involved in RNA binding. NMR data showed that the RNA substrate interacts only with the dimeric conformation of the protein (Supporting Information Fig.…”
Section: Active Conformationmentioning
confidence: 99%
See 2 more Smart Citations
“…These mutation to the surface of cancer cells (Moll et al 2001). Coiled-coil proteins have been extensively investigated using various experimental techniques such as NMR (Nikolaev and Pervushin 2007), X-ray diffraction (O'Shea et al 1991), circular dichroism (CD) and fl uorescence spectroscopy (Suzuki et al 1998), differential scanning calorimetry (DSC) (Yu et al 1996) and electron spin resonance (ESR) spectroscopy (Columbus and Hubbell 2004) as well as theoretical and computational approaches using molecular dynamics (MD) simulation techniques (Mohanty et al 1999;Missimer et al 2005;Pineiro et al 2005). MD simulations provide a means to understand the structural and dynamic behavior of coiled-coil at the atomic level which is often inaccessible to experimental tools.…”
Section: Peptide Designmentioning
confidence: 99%